Media Poster Sebagai Promosi Perilaku Hidup Sehat untuk Mengatasi Diare di Masyarakat RT 02 RW 17, Kelurahan Tambakrejo, Kecamatan Tempel, Kabupaten Sleman, D.I Yogyakarta - Wardani, Yuniar; Khalifah, Umi (Universitas Pahlawan Tuanku Tambusai, 2023)
under the age of 5 in the world in general and in developing countries. Some of the factors that because diarrheal disease is caused by bacteria through contamination of food and drink contaminated with feces and or direct contact with sufferers. Other causes include the environment and household. Efforts to prevent and treat diarrhea must be understood by the community. Health intervention programs should be designed to promote healthy behavior to reduce the burden of diarrhea should be easily accessible, and affordable to the public. Health promotion in the form of counseling using poster media with the aim of providing knowledge and learning about diarrheal diseases to the community in RT 02 RW 17, Tambakrejo Village, Tempel District, Sleman Regency, D.I Yogyakarta is one of the solutions. Keywords: Diarrhea, Promotion, Health, Poster